A legal analysis on the adequacy of Witness Protection Act 2009 in protecting witnesses in Malaysia / Nur Amira Ruslan …[et al.] - Ruslan, Nur Amira; Ruslan, Rasyidah; Azhar, Norazira; Md Shuhaimi, Nursuhaida (2014)
The objective of this research is to improvise the effectiveness of the Witness Protection Act 2009 in protecting witness in Malaysia. This research is purely doctrinal and is library-based in which we seek to find out the gaps of the system based on the Act construction and suggest improvements. It is an analytical and critical study with partly comparative studies where comparisons are done with the Witness Protection Program in our country with the ones in countries like United States, Philippines and Canada. Based on our findings, it can be seen that the aspects which may have room for improvements are in regard to the potential participants aka witness, procedure for application to be included in the program, possible areas for relocation and budget allocation for the program. It is highly recommended that the secrecy of this Program should be loosened in terms of general knowledge about this Program and other aspects which will be discussed in lengthy.